Political economy of water - Tiwari, Aparna (Jaipur : Rawat Publications, 2020)
Water is the lifeline of humankind. Its use and abuse determine the course of development. When almost all the communities are hierarchical, its access, distribution, and management become very crucial to the survival and development of the human race. The present book discusses the issues of control over water and its equal distribution in the rural community of Central Uttar Pradesh. Based on empirical research, it unravels the dynamics of water control and use in two canal irrigated villages which reveals different realities of canal and groundwater irrigation. It articulates that although social hierarchy, i.e. caste, class and gender are detrimental to access to and control over water leading to dominance and conflicts, mutual negotiations over the distribution of water is everyday routine for villagers.
Includes bibliographical references and index.
Keywords: Water use -- Nasratpur; Water use -- Bhelai Khurd; Water rights -- India -- Nasratpur; Water rights -- India -- Bhelai Khurd; Residential water consumption -- Nasratpur; Residential water consumption -- Bhelai Khurd